EIB Complaints Mechanism Report 2021 - European Investment Bank (2022)
"Are you curious to learn how the EIB Group Complaints Mechanism (EIB-CM) has been addressing concerns of the public regarding EIB Group's projects or activities? Have a look at its Activity Report for 2021. 2021 remained particularly challenging, also because of the continuing COVID-19 pandemic. The EIB-CM registered 64 new cases, handled a total of 107 cases and closed 64 of them. With 71% the vast majority of cases open at year-end were registered in 2021. The EIB-CM managed to close several complex cases containing a range of environmental and social allegations such as the Curtis Biomass Power Generation Plant (Spain), Nepal Power System Expansion (Nepal), GEEREF/Akiira Geothermal Power Plant (Kenya), Budapest Airport Concession (Hungary) and Toplofikacia CHP (Bulgaria). The EIB-CM continues to play a vital role as the EIB Group's accountability function."